Review of HPLC Methods for Determination of Azithromycin in Different Samples (Iraqi Journal of Medical Sciences, 2022)
Azithromycin is a semi-synthetic macrolide antibiotic of the azalide groups. It inhibits bacterial protein synthesis by binding to the 50S ribosomal subunit of the bacterial 70S ribosome. It inhibits peptidyl transferase activity and interferes with amino acid translocation during the process of translation. Its effect may be bacteriostatic or bactericidal depending on the organism and the drug concentration. Azithromycin is one of the famous and important antibiotics agents and the determination methods of azithromycin in this article were tabulated with lots of chemical and instrumental methods that used in different parameters. Different high performance chromatographic methods have been reviewed in this paper.Keywords: Azithromycin, HPLCCitation: Taqi RMM, Hammoudy SR, Hamzah MJ. Review of HPLC methods for determination of azithromycin in different samples. Iraqi JMS. 2022; 20(1): 77-82. doi: 10.22578/IJMS.20.1.10
Keywords: Azithromycin; HPLC